Біологічна активність культур ціанобактерій та їх фаголізатів - Менджул, М.І.; Лисенко, Т.Г.; Бусахіна, І.В.; Андрієнко, О.В. (Видавничий дім "Академперіодика" НАН України, 2008)
The antifungal activity of cyanobacterial cultures of different taxonomic groups and phage lysates of these bacteria against some phytopathogenic fungi of garden plants and fungi that cause powdery mildew has been studied. It is established that cyanobacterium Plectonema boryanum and its phage lysate LPP-3 had high activity in vitro only against one pathogen - Botritys cinerea. Cyanobacterium Anabaena variabilis and its phage lysate А-1 are toxic against two pathogens - B. cinerea and Marssonina rosea. Cyanobacterium Synechococcus cedrorum and its phage lysate S-8K are the most active against all three pathogens. Phage lysate S-8K causes practically 100% death of fungal mycelium - the agent of powdery mildew on infected plants of tobaccos, cucumbers, roses on closed ground, and apple-trees and dahlias in open ground. In view of the high antifungal action of phage lysate S-8K, it can be recommended as perspective in the development of antifungal preparations with a wide spectrum of action.